10.18081/2333-5106/2022.10/136 (American Journal of BioMedicine, 2022)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders characterized by social deficits, communication inabilities and stereotypic behaviors. There are many suspected genetic causes of autism, but no cure has been proven to work to treat the disorder. Stem cells have been studied for their potential role in treating ASDs. Twenty-five children who fulfilled the autism criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition [total scores below 30 indicate that an individual is “non-autistic,” while scores of 30 or above indicate that an individual is “autistic.” Individuals with scores above 30 are further subdivided into having “mild to moderate autism” (30 to 36.5) or “severe autism” (37 to 60)]. In this study only Childhood Autism Rating Scale (CARS) scores >37 was participated in this study. Harvested bone marrow from posterior iliac crest under light general anesthesia, for all patients under 10 kg collected 6 ml/kg while calculated the volume above 10-year age group (60 ml + [body weight in kg − 10] × 7 ml). Isolated mononuclear cells through Ficoll gradient under sterile condition in laminar flow class 2. The end products transmitted to sterile tube and injected slowly intrathecally. The same procedure was repeated 3 months later. The result after first bone marrow transplant showed that no severe side effects related with these procedures. The median CARS score decreasing from 52 to 44.2 (P =0.02). Beside this data the severity of autism spectrum disorder signs and symptoms were reduced. Inconclusion, this resulted data suggested that stem cell therapy for children with autism might be safe and effective. However, the evidence was compromised by the limitations in current study size, lacking standardized injection routes and doses of stem cells, as well as shortages in diagnostic tools and long period follow-up studies.